2002
DOI: 10.3171/jns.2002.97.2.0293
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complications associated with the endoscopic endonasal transsphenoidal approach for pituitary adenomas

Abstract: Transsphenoidal surgery, either microscopic or endoscopic, is a safe procedure in experienced hands, but serious complications still occur and must be reduced as much as possible. Additional improvement can be expected with greater experience and new technical developments. A coordinated team effort with other dedicated colleagues from different specialties is advised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
329
8
30

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 474 publications
(393 citation statements)
references
References 31 publications
26
329
8
30
Order By: Relevance
“…The reported complication rates of TSS are 9.1%, 23.4% and 22.1% [1,14,16], which are far higher than ours. Damage to the carotid artery leads to serious complications ( Table 6).…”
Section: Complicationscontrasting
confidence: 47%
See 2 more Smart Citations
“…The reported complication rates of TSS are 9.1%, 23.4% and 22.1% [1,14,16], which are far higher than ours. Damage to the carotid artery leads to serious complications ( Table 6).…”
Section: Complicationscontrasting
confidence: 47%
“…Damage to the carotid artery leads to serious complications ( Table 6). Cappabianca et al and Gondim et al reported carotid artery injury rates of 0.7%-0.9% [14,16]. Preventing such damage might thus be one advantage of endoscopic TSS with navigation [17].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clinical investigations [14,15] suggested that the learning curve to grasp the endoscopic pituitary surgery required 40 to 80 operations. We consider this number never enough for a surgeon to be proficient in the practice of nasal endoscope.…”
Section: Discussionmentioning
confidence: 99%
“…In the pituitary surgery, the procedure by nasal endoscope has a lot of advantages that microscope can't afford [3][4][5][6][7][8][9][10][11][12][13][14][15]17], though it also has several disadvantages, however which will be overcomed along with the continuously developing of new instruments and new techniques.…”
Section: Discussionmentioning
confidence: 99%